Carnaval belenense em tempos de Estado Novo (1938-1946) - Teixeira, Tatiane do Socorro Correa (2013)
This study, Belenense Carnival in Times New State (1938-1946), aims to understand the belenense carnival mid-1938 to 1946 in a time when the Estado Novo regime will act on demonstrations across the country carnival. Aims to present a carnival beyond the control focusing on grassroots resistance when they sought numerous ordinances restrict their spontaneity in the days of carnival revelry. It proposes to submit like the Departamento Estadual de Imprensa e Propaganda do Pará (DEIP) acted changing the face belenense Carnival, with its rules and regulations established by the regime in an attempt to control over the carnival groups that disagreed its purposes. Objective know Rancho Não Posso me Amofiná throughout its history, memory and resistance in the belenense carnival. Thus, this thesis proposes techniques from oral history and the intersection with written sources, composing a framework of analysis and interpretation that enables the understanding belenense carnival in the context of the Estado Novo Regime in Belém